Droit pénal et crimes en Algérie : les alibis du pénal - Damien Scalia (Criminocorpus)
Criminal law is increasingly presented as a possible response to colonial crimes. Its advocates and architects put forward many purposes in its defence: penological objectives, historical challenges, the symbolic function, moral expectations and the cathartic effect. But these elements of legitimisation are mainly alibis, i.e. means of defence signifying that it is simply in the right place at the right time. It is important to remember, however, that these alibis often do not hold water... not to exclude criminal law from the issue of colonial crimes, but to put it back in its place.